Epistemic Vigilance and the Science/Religion Distinction - Talmont-Kaminski, Konrad (Journal of cognition and culture, 2020)
Both science and religion are human endeavours that recruit and modify pre-existing human capacity to engage in epistemic vigilance. However, while science relies upon a focus on content vigilance, religion focusses on source vigilance. This difference is due, in turn, to the function of religious claims not being connected to their accuracy - unlike the function of scientific claims. Understanding this difference helps to understand many aspects of scientific and religious institutions.